1999
DOI: 10.1001/archneur.56.11.1348
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Creatine Kinase–BB Isoenzyme Activity and Outcome After Subarachnoid Hemorrhage

Abstract: The level of CSF CK-BB may help predict neurologic outcome after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In SAH, acceptable sensitivities and specificities were demonstrated with CRP, selectin, thrombin antithrombin complex (TAT), creatine kinase-BB (CK-BB) and malondialdehyde (MDA) (83 versus 84%, 90 versus 83%, 72 versus 70%, 70 versus 100% and 88 versus 75%, respectively) (Coplin et al, 1999; Jeon et al, 2012; Kaneda et al, 2010; Morga et al, 2007; Wang et al, 2011). Although most of the sensitivities and specificities are not greater than 90%, each of these markers may be able to identify subjects that have poor outcome and those that will potentially recover well with some reasonableness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In SAH, acceptable sensitivities and specificities were demonstrated with CRP, selectin, thrombin antithrombin complex (TAT), creatine kinase-BB (CK-BB) and malondialdehyde (MDA) (83 versus 84%, 90 versus 83%, 72 versus 70%, 70 versus 100% and 88 versus 75%, respectively) (Coplin et al, 1999; Jeon et al, 2012; Kaneda et al, 2010; Morga et al, 2007; Wang et al, 2011). Although most of the sensitivities and specificities are not greater than 90%, each of these markers may be able to identify subjects that have poor outcome and those that will potentially recover well with some reasonableness.…”
Section: Resultsmentioning
confidence: 99%
“…CK-BB is a creatine kinase found in the brain and is involved in energy maintenance within mitochondria. Coplin et al (1999) demonstrated that increased CSF levels of CK-BB, greater than 40 U/L, was associated with unfavorable outcome at 1 week and 2 months after SAH.…”
Section: Discussionmentioning
confidence: 97%
“…In the work of Coplin et al [12], in which a cutoff value of 40 U/L was used for CK-BB level, the sensitivity and specificity of 70% and 100% were determined respectively for subarachnoid hemorrhage in general. However, Briem H et al [13], have indicated that the determination of the CK-BB activity in the CSF is not useful in differentiating diagnosis but in only the prognosis of bacterial and viral meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…The brain has many isoforms CKBB and mitochondrial-CK but lacks CKMB and CKMM, respectively found in the cardiac and skeletal muscles. (34) The molecular mass of CKBB is 40 to 53 kDa. (16) CK-BB is located in the astrocytes and is released when there is anatomical injury in the brain tissue.…”
Section: Glial Fibrillary Acidic Proteinmentioning
confidence: 99%
“…(16) Various situations of brain injury such as cardiac arrest and subarachnoid hemorrhage may lead to release of CKBB in the liquor. (34) High CKBB serum levels are also found in adenocarcinomas of the prostate, breast, ovary, colon, other adenocarcinomas of the gastrointestinal tract and also in small cell anaplastic carcinoma of the lungs. (35) Severe TBI studies have disclosed correlation of the severity score assessed by GCS with serum levels of CKBB.…”
Section: Glial Fibrillary Acidic Proteinmentioning
confidence: 99%